Tridimensional Visualization through Optical Illusion - Silva, Vinícius Emanuel Miranda; Almeida, Mozart William Santos; Teixeira, João Marcelo X. N.; Teichrieb, Veronica (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
Holography is a technique that uses the properties of light as a way of registering and representing three-dimensional scenes and objects. However, holography is not the only technique that makes it possible to visualize in three dimensions. In this work will be detailed another form of three-dimensional visualization based on an invention of the late 19th century. Different applications that use this approach will be presented, as well as their results that are quite similar to those of holography. A solution involving hardware/software for 3D visualization through optical illusion is proposed. Using a prism with specific geometric proportions, is possible project the generated content with the developed tool to visualize objects and even 3D point clouds relating to faces captured with the Microsoft Kinect sensor.